VORTEX STRUCTURE OF THE FLOW AND ANALYSIS OF DIFFERENT MATHEMATICAL MODELS OF FLOW IN CHANNELS OF HIGH-RADIAL-AXIAL HYDRAULIC TURBINES RО 400, RО 500 AND RО 600 - Потетенко, Олег Васильевич; Дранковский, Виктор Эдуардович; Гришин, Олександр Мефодійович; Крупа, Евгений Сергеевич; Вахрушева, Ольга Сергеевна (Eastern-European Journal of Enterprise Technologies, 2012)
The analysis of the causes of the origination complex swirl structure of the flow and high energy losses is carried out , analysis of different mathematical models in the channels of high-pressure RO water turbines also.